Factors that contribute to customer satisfaction towards service quality: a case study on Damai Harmoni housing project developed by PKNS / Mohd Irmee Abdul Karim - Abdul Karim, Mohd Irmee (Faculty of Business and Management, 2005)
Although service quality and customer satisfaction is related concepts, they are not exactly the same things. The customer's perception about service quality is based on long term, cognitive evaluations of PKNS's service delivery, whereas customer satisfaction is a short term emotional reaction to a specific service experience. Before the customers purchase a service or a product, they have an expectation about its quality that is based on individual needs, past experience and worth of mouth communication . Service or product is also essential that the company look at it as the distinguishing aspect of what they do. It is really important to the companies that can set them apart from their competitors. This research is about "Factors that contribute to customer satisfaction towards service quality: A case study on Damai Harmoni housing project". This research is done to identify: (1) the level of customer satisfaction toward PKNS products and services, (2) the factors that could fulfill customer satisfaction in buying a house, (3) to study customer's perception towards service quality and (4) to give suggestions and recommendations as to what can be done to enhance customer satisfaction at PKNS Bangi. With the results of this research, it is able to provide PKNS's employees with the useful of information to improve their service quality in order to give maximum customer satisfaction. A set of 80 questionnaires were distributed to the respondents who had purchased Damai Harmoni houses. This research is focusing only on the buyers of Damai Harmoni houses and it is about 39 of questions were asked to the respondents to gather an accurate information. Software SPSS version 11.5 was used to analyze the data in terms of frequency and cross tabulation. All of this information is analyzed and most of the respondents said that the service is not match with their expectations and the company still needs to enhance their service quality. Moreover it shows that PKNS Bangi, as a housing developer should find out an alternative action to make improvement from time to time. In addition, recommendations and suggestions are made about the quality of service and product provided by PKNS Bangi based on the feedback of the respondents. It is hoped that all the recommendations and suggestions will help the company to generate ideas to detennine the new strategy to be implement in the future.